Acromegaly Clinical Trial Methodology Impact on Reported Biochemical Efficacy Rates of Somatostatin Receptor Ligand Treatments: A Meta-Analysis - Carmichael, John D. (Endocrine Society, 2014)
INTRODUCTION: Biochemical efficacy of somatostatin receptor ligand (SRL) treatment in acromegaly is defined by metrics for GH and IGF-1 control. Since the earliest therapeutic trials, biochemical control criteria, medical formulations, and assay techniques have evolved. MATERIALS AND METHODS: We searched PubMed for English-language trials published from 1974 to 2012 evaluating 10 or more patients, with a duration of more than 3 months and biochemical control as a key objective. We used a random-effects model to compare biochemical outcomes for octreotide and lanreotide trials according to study design characteristics. RESULTS: A total of 4464 patients were enrolled in the analyzed trials; 4125 were treated, and 3787 completed study treatment. Overall achieved control rates were 56% for mean GH and 55% for IGF-1 normalization. Treatment duration was significantly related to both GH (P < .001) and IGF-1 control (P = .02). Prior SRL therapy (P = .01), and year of study publication (P = .03) were related to biochemical control for GH but not IGF-1. No statistically significant differences in GH or IGF-1 response rates were observed for multicenter vs single center, retrospective vs prospective, study drug, and preselection for SRL responsiveness. Dosing scheme, GH response criterion, or switch study design were also not statistically significant in determining GH or IGF-1 response rate. CONCLUSIONS: Clinical design characteristics anticipated to impart efficacy bias including switching, preselection for SRL responsiveness, and retrospective design had no statistically significant impact on efficacy determination. Later year of publication, study duration, and prior SRL use are significant efficacy determinants for acromegaly trial outcomes.